“Did I choose the right University?” Examining the Influence of Post-Purchase Cognitive Dissonance on Word-of-Mouth Behaviours among University Students in the UK. - Pursnani, Natasha (2020)
Research on post-purchase cognitive dissonance has provided marketers with valuable information over the years, with many authors applying Leon Festinger's (1957) ground-breaking "Theory of Cognitive Dissonance" to various contexts and industries. However, there remains little understanding of how psychological experience of dissonance affects other consumer actions, such as word of mouth. Moreover, application of the theory within marketing has predominantly focused on tangible products and goods, whilst side-lining experiences of dissonance in high involvement services contexts including the University experience. For this reason, this study aims to investigate the influence of post-purchase cognitive dissonance on word of mouth behaviour. The study’s participants included 117 students studying at a University in the UK and were requested to complete an online questionnaire survey. The findings of the study suggest there are various factors (antecedents) leading University students to experience cognitive dissonance, and this influences the valence, nature, richness, strength of delivery, volume, and number of contacts of WoM behaviours they engage in. Furthermore, culture was not found to have a significant influence on students' behaviour. Implications for marketers operating in the UK’s higher education industry are highlighted, to help them understand effective ways of managing post-purchase dissonance and encouraging positive WoM behaviours.